Model Pembelajaran Kooperatif Dalam Pembelajaran IPS - Setiyani, Setiyani (Universitas Sebelas Maret, 2020)
This research is motivated by an interest in seeing the application of cooperative learning models in social studies learning with the formulation: 1) Achievement of the application of cooperative learning models in social studies learning ?, and 2) Factors - what factors are constraints in applying cooperative learning models to social studies learning ?. The data analyzed in the research comes from the publication of scientific works that have been studied first. Data search is done by using the keyword